2020
DOI: 10.1371/journal.pone.0243617
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing trend of imported malaria cases but increasing influx of mixed P. falciparum and P. vivax infections in malaria-free Kuwait

Abstract: Malaria still continues to be the most important parasitic disease worldwide, affecting 228 million people and causing 405,000 deaths each year. In this retrospective study during 2013 to 2018, we documented the incidence of imported malaria infection and evaluated the impact of malaria preventive measures in Kuwait, a non-endemic country. The epidemiologic and demographic data of all malaria cases was collected from the Infectious Diseases Hospital, Kuwait where all suspected cases of malaria are referred for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 33 publications
1
39
0
Order By: Relevance
“…These cases were either newly arriving expatriate workers from endemic countries or resident workers who were returning to Kuwait after visiting their native countries [ 42 , 43 , 44 , 45 , 46 ]. However, the data from these and a more recent study have shown a declining trend in the incidence of imported malaria cases in Kuwait [ 26 , 43 , 45 ].…”
Section: Epidemiology Of Malaria Among Gcc Countriesmentioning
confidence: 99%
See 4 more Smart Citations
“…These cases were either newly arriving expatriate workers from endemic countries or resident workers who were returning to Kuwait after visiting their native countries [ 42 , 43 , 44 , 45 , 46 ]. However, the data from these and a more recent study have shown a declining trend in the incidence of imported malaria cases in Kuwait [ 26 , 43 , 45 ].…”
Section: Epidemiology Of Malaria Among Gcc Countriesmentioning
confidence: 99%
“…The study carried out in the last decade in Kuwait reported nearly 250–400 malaria cases annually and all cases represented imported malaria cases. A vast majority of cases were detected among expatriates and 80% of cases occurred among male expatriates aged 21–40 years [ 26 ]. P. vivax was responsible for 71% of malaria cases while P. falciparum infections accounted for 27% of malaria cases in Kuwait [ 26 ].…”
Section: Epidemiology Of Malaria Among Gcc Countriesmentioning
confidence: 99%
See 3 more Smart Citations